Semiotic Construction of Cyberbullying in the Budi Pekerti Trailer: Konstruksi Semiotik Cyberbullying dalam Trailer Budi Pekerti - Wahyullah, Idam; Fikri, M. Andi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Cyberbullying has become a prevalent issue in the digital era, facilitated by the rapid spread of information through social media. Specific Background: The Indonesian film Budi Pekerti portrays this phenomenon through its narrative, with the trailer highlighting scenes that depict public judgment and online harassment. Knowledge Gap: While prior studies have explored cyberbullying representation in films and social campaigns, limited research has examined how meaning construction emerges from cinematic trailers using semiotic analysis. Aims: This study investigates how visual, textual, and auditory signifiers in the Budi Pekerti trailer represent cyberbullying (signified) and construct meaning that shapes audience perspectives. Results: Using Ferdinand de Saussure’s semiotic theory and a descriptive qualitative method, the analysis reveals that incomplete video clips in the trailer function as signifiers, prompting varied audience interpretations that often align with negative judgments toward the protagonist, Mother Prani. Novelty: This study demonstrates how a film trailer, as a condensed narrative, can serve as a powerful medium for constructing and circulating meanings about social issues, particularly cyberbullying. Implications: Findings highlight the role of media framing in influencing public opinion, underscoring the importance of critical media literacy to prevent misinterpretation and online harassment. Highlights: Semiotic analysis of visuals, subtitles, and sounds. Trailer framing shapes audience interpretation. Highlights media literacy in preventing misjudgment. Keywords: Cyberbullying, Semiotics, Meaning Construction, Film Trailer, Budi Pekerti